Early application of extracorporeal membrane oxygenation for myocarditis with shock: a case report - Heyu Meng (SAGE Publishing, 2021)
The current therapy for myocarditis is immunosuppressive therapy. However, in rare cases in which patients do not respond to intervention, their condition can rapidly deteriorate to myocarditis with shock, which is characterized by extensive and diffuse lymphocyte infiltration in the myocardium. Most cases of myocarditis are caused by virus-mediated damage of cardiomyocytes, and its clinical manifestations are ventricular arrhythmia and hemodynamic disturbances. Extracorporeal membrane oxygenation is an effective intervention, which regulates hemodynamic stability and avoids systemic hypoperfusion. This intervention has been used to sustain hemodynamic stability in patients with myocarditis and shock. We report here early application of extracorporeal membrane oxygenation for successful treatment of a patient with myocarditis and shock.